A novel virulence strategy for Pseudomonas aeruginosa mediated by an autotransporter with arginine-specific aminopeptidase activity - Luckett, Jeni; Darch, Owen; Watters, Chase; AbuOun, Manal; Wright, Victoria; Paredes-Osses, Esteban; Ward, Jenny; Goto, Hana; Heeb, Stephan; Pommier, Stéphanie; Rumbaugh, Kendra P.; Cámara, Miguel; et al. (2012)
The opportunistic human pathogen, Pseudomonas aeruginosa, is a major cause of infections in chronic wounds, burns and the lungs of cystic fibrosis patients. The P. aeruginosa genome encodes at least three proteins exhibiting the characteristic three domain structure of autotransporters, but much remains to be understood about the functions of these three proteins and their role in pathogenicity. Autotransporters are the largest family of secreted proteins in Gram-negative bacteria, and those characterised are virulence factors. Here, we demonstrate that the PA0328 autotransporter is a cell-surface tethered, arginine-specific aminopeptidase, and have defined its active site by site directed mutagenesis. Hence, we have assigned PA0328 with the name AaaA, for arginine-specific autotransporter of P. aeruginosa. We show that AaaA provides a fitness advantage in environments where the sole source of nitrogen is peptides with an aminoterminal arginine, and that this could be important for establishing an infection, as the lack of AaaA led to attenuation in a mouse chronic wound infection which correlated with lower levels of the cytokines TNFα, IL-1α, KC and COX-2. Consequently AaaA is an important virulence factor playing a significant role in the successful establishment of P. aeruginosa infections.